2016
DOI: 10.1371/journal.pone.0156109
|View full text |Cite
|
Sign up to set email alerts
|

WNT7A Regulation by miR-15b in Ovarian Cancer

Abstract: WNT signaling is well known to play an important role in the regulation of development, cell proliferation and cell differentiation in a wide variety of normal and cancerous tissues. Despite the wealth of knowledge concerning when and where various WNT genes are expressed and downstream events under their control, there is surprisingly little published evidence of how they are regulated. We have recently reported that aberrant WNT7A is observed in serous ovarian carcinomas, and WNT7A is the sole ligand acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…Aberrant regulation of miR-15b plays a key role in cell proliferation, angiogenesis and metastasis in a variety of tumours [26]. According to the previous studies, miR-15b has displayed decreased expression [6][7][8][9][10][11][12] or increased expression [17][18][19][20][21] in human tumours. Even, miR-15b harbours the opposite expression levels in the same tumour tissues, such as glioma [7,18], indicating that its expression level is related with the specific types of tumour tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant regulation of miR-15b plays a key role in cell proliferation, angiogenesis and metastasis in a variety of tumours [26]. According to the previous studies, miR-15b has displayed decreased expression [6][7][8][9][10][11][12] or increased expression [17][18][19][20][21] in human tumours. Even, miR-15b harbours the opposite expression levels in the same tumour tissues, such as glioma [7,18], indicating that its expression level is related with the specific types of tumour tissues.…”
Section: Discussionmentioning
confidence: 99%
“…We have found high enrichment of microRNAs after 20 days of Lp (a) treatment in HAVICs. Among those identified were miR-130a and miR-15B, which are known to regulate Wnt signalling [40,41] and are identified as biomarker of atherosclerosis obliterans [42]. miR-154 was found to be a biomarker for CAD [43]; and miR216A has roles in osteogenesis and cholesterol efflux via PI3K/AKT pathway [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of endogenous and small noncoding RNAs with 21–23 ribonucleotides, which can induce mRNA degradation or act as repressors of translation through directly binding to a target site in the 3′‐untranslated regions of their target genes. Existing studies found that miRNA mediated gene regulation involved in multiple pathological processes including cell proliferation, differentiation, migration, survival, and tumorigenesis . Recent evidence has shown that miRNAs also plays a vital role in chemotherapeutic resistance.…”
Section: Introductionmentioning
confidence: 99%